The Effects of Some Drugs Used to Treat Honeybee (Apis mellifera L.) Diseases and Pests on Lifespan of Honeybees - Duran Özkök; Ethem Akyol (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted to determine the effects of Bayvarol®, Fumidil-B®, Neo-Terramycin® on adult honeybee lifespan. Total twenty honeybee colonies were used and randomly divided into four groups (each group consisted of five colonies). Experimental groups: Bayvarol ®, Fumidil-B® and Neo-Terramycin® were treated to first, second and third groups, respectively. No treatment was done to forth group taken as control group. A hundred one day old worker bees were taken from each group and marked with different colors and numbered on the thorax. After the marked, all worker bees were given into the observation hive. Marked worker bees were controlled and counted daily. Statistical analysis of data was done by variance analysis method and between groups comparisons were done with Duncan's multiple range tests. Average lifespans of the first, second, third and control groups were 44.97±4.90, 46.86±6.56, 45.38±6.12 and 47.72±6.06 days, respectively. There were found statistically significant differences among average lifespan of first, second, third and control groups. This study showed that some drugs used to treat diseases and pests reasoned a negative effect on the lifespan of honeybees.